2015
DOI: 10.5392/jkca.2015.15.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Suggestions of Improvements on Visual Information System in Subway Transfer Station -Mainly with Service for Destination Information in Sindorim Station-

Abstract: The subway is one of the representative urban public transportation systems. Since its being opened in 1974, the Seoul Subway has been continually extended, and new lines are being added in the metropolitan and outskirt areas, even at present. As a result, the numbers of transfer stations and transfer sections have been significantly increased, making the usage of the subway system more and more complicated. In the transfer stations with big floating population and overlapped flows of traffic in the subway, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[ 11 , 12 ]. Efficient planning for users is important in public transportation [ 13 ], and In and Choe [ 14 ] conducted a study on a subway space, which is a representative public transportation method. It was confirmed that in complicated subway transfer sections (Sindorim Station, Seoul), factors that make wayfinding difficult include a lack of information transmission of the visual information system that provides information to users and its complex arrangement, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 , 12 ]. Efficient planning for users is important in public transportation [ 13 ], and In and Choe [ 14 ] conducted a study on a subway space, which is a representative public transportation method. It was confirmed that in complicated subway transfer sections (Sindorim Station, Seoul), factors that make wayfinding difficult include a lack of information transmission of the visual information system that provides information to users and its complex arrangement, etc.…”
Section: Introductionmentioning
confidence: 99%